Study on Antibiotic Resistance Profiles Exhibited by Vibrio Species Isolated from Landfill Soils in Zaria Metropolis, Northern Nigeria - Yomi Marie Carole Nyandjou; Abubakar Umar (UMYU Journal of Microbiology Research)
Study’s Novelty/Excerpt